Odpowiedzi

2010-01-15T12:11:45+01:00
Odpowiedzi przesyłam w załącznikach
Pozdrawiam
Najlepsza Odpowiedź!
2010-01-15T13:41:46+01:00
A)
y+2-(3-x)=0
x-2=5-(2-y)

y + 2 - 3 + x = 0
x - 2 = 5 - 2 + y

x + y = 3 - 2
x - y = 5 - 2 + 2

x + y = 1
x - y = 5

sumujemy stronami
x + y + x - y = 1 + 5
2x = 6
x = 3

x + y = 1
y = 1 - x
y = 1 - 3
y = -2

B)
3(x-y)+4x=8
3(x-5y)=5-9y

3x - 3y + 4x = 8
3x - 15y +9y = 5

7x - 3y = 8 | *(-2)
3x - 6y = 5

-14x +6y = -16
3x - 6y = 5

sumujemy stronami
-11x = -11
x = 1

-14x + 6y = -16
6y = -16 + 14x
6y = -16 + 14
6y = -2
y = -1/3

C)
3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+12

6x - 3 + 4y - 8 = 9
10x - 2 + 3y = 15x + 5y + 12

6x + 4y = 9 + 3 + 8
10x - 15x + 3y - 5y = 12 + 2

6x + 4y = 20
-5x - 2y = 14 |*2

6x + 4y = 20
-10x - 4y = 28

sumujemy stronami
-4x = 48
x = -12
4y = 20 - 6x = 20 + 6*12 = 116
y = 29
2010-01-15T15:26:00+01:00
A)
y+2-(3-x)=0
x-2=5-(2-y)

y+2-3+x=0
x-2=5-2+y

y+x=0-2+3
x-y=5-2+2

y+x=1
x-y=5
_______
y+x+x-y=6
2x=6
x=3

y+3=1
x=3

y=-2
x=3

b)

3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8
3x-15y+9y=5

7x-3y=8 /*-2
3x-6y=5

-14x+6y=-16
3x-6y=5
___________
-14x+6y+3x-6y=-11
-11x=-11
x=1


7*1-3y=8
x=1

-3y=8-7
x=1

-3y=1
x=1

y= -1/3 <-- minus jedna trzecia .
x=1

c)

3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=9+8+3
10x+3y-15x-5y=2+2

6x+4y=20 /:2
-5x-2y=4

3x+2y=10
-5x-2y=4
____________
3x+2y-5x-2y=14
-2x=14
x=-7

3x+2y=10
x=-7

-21+2y=10
x=-7

2y=31
x=-7

y=15,5
x=-7